Road to a bioeconomy in the European Union: Mapping drivers of precision fermentation adoption - Niklas Thomas Starz (Junior Management Science (JUMS), 2024)
The escalating crisis of climate change, biodiversity loss, and pollution necessitates urgent shifts in production and consump-tion patterns towards enhanced environmental efficiency (EE). Western governments, including the European Union (EU),advocate transitioning to a bioeconomy based on renewable resources and free from fossil fuels. A pivotal technology in thisshift is precision fermentation (PF), which employs synthetic biology to transform microbes into 'cell factories' capable ofproducing diverse goods from renewable feedstocks. Despite its introduction in 1982, PF's impact on EU production processeshas been limited. This paper, drawing on Geel's (2002) concept of technology transformations as sociotechnical phenomena,explores the drivers and barriers to PF adoption through interviews with eight biomanufacturing ecosystem experts. Findingsreveal a dynamic niche propelled by advances in synthetic biology, environmental pressures, and global supply chain dis-ruptions. However, substantial internal barriers at both niche and system levels hinder transformative progress, underliningcritical areas for EU policy intervention. This paper provides strategic insights for policymakers, established companies, andentrepreneurs aiming to navigate the transition to a bioeconomy.
Keywords: 650; biomanufacturing; EU bioeconomy strategy; multi-level perspective; precision fermentation